Application of Neural Network Overview In Data Mining - Rahardian, Rifky Lana; Sudarma, Made (International Journal of Engineering and Emerging Technology; Vol 2 No 1 (2017): January - June, 2017)
Data Mining is the term used to describe the process extract value / information from the database. Four things are needed in order to effectively data mining: data that has a high quality, right of data, examples of which are adequate, and the correct device. To obtain valuable information in the required data mining algorithms applied in data mining in large databases. There are a lot of complex algorithms in data mining. One is the so-called Neural networks have an important role in data mining.